Boron and gadolinium neutron capture therapy for cancer treatment - Hosmane, Narayan S. (World Scientific Pub. Co., 2012)
The book focuses on two concurrent experimental therapies in cancer treatment known as boron neutron capture therapy (BNCT) and gadolinium neutron capture therapy (GdNCT) using a variety of boron- and gadolinium-based compounds. Some of the gadolinium compounds serve the dual purpose as being MRI contrast agents and GdNCT agents. The book describes why BNCT & GdNCT were not at the forefront of the clinical trials during the past seven to eight decades since the discovery of neutrons by John Chadwick in 1932 and how the latest development in the synthesis of target boron- and gadolinium-based d.